Penerapan Metode Data Envelopment Analysis Untuk Mengukur Efisiensi Relatif Usaha Sapi Perah Anggota Koperasi - Sabrina, Ahsana Maryama; Hadiana, Muhammad Hasan; Daud, Andre Rivianda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Data envelopment analysis (DEA) measures technical efficiency every single of production decision-making units (DMU) in a population. This analysis produces parameters in the form of an inefficiency index that can be used to rank the performance of each DMU. This study tries to apply the above method to dairy farms that are members of a cooperative, aiming to obtain a measure of the technical efficiency index of the observed sample farms and then test how close the relationship is between the efficiency index and other parameters, namely  farm size or the number of dairy cows and income based on the income over feed cost measure (IOFC). The research was conducted using a survey approach among KPBS Pangalengan dairy cooperative members. The survey applied multi-stage sampling to select randomly 95 farmers sample of the cooperative members. Data analysis used Stata 17 software. The results showed that the relative technical efficiency index for dairy farming spread from the lowest, namely 0.2 to 1 (fully efficient); overall, the distribution of the efficiency index followed a distribution next to the standard curve. 13.7% of farmers achieved full efficiency  The research results show that IOFC ranges from IDR 527,821 to IDR 260,462,313/year, and the scale of cattle ownership ranges from 1 to 15 cows. The variations in these two parameters have a significant positive correlation. Farmers with a large dairy farm size and IOFC tend to have a high-efficiency index, with strong and weak levels of closeness (r = 0.609 and r = 0.356).